Türkiye'deki inflamatuar barsak hastalarında HLA-DRB1 alellerinin dağılımı - (:unkn) unknown (My University, 2000)
Ülseratif kolit (ÜK) ve Crohn hastalığı (CH) ile HLA sınıf II genleri arasında son. yıllarda tanımlanan farklı ilişkiler hastalığa yatkınlıkta genetik çeşitlilik olduğunu düşündürmektedir. Bu çalışmada, Türkiye popülasyonunda CH (n=15) ve ÜK (n=59) hastalarındaki HLA-DRB1 alelleri sağlıklı kontrollerle (n=244) karşılaştırılarak incelendi. Polimeraz zincir reaksiyonu ve diziye özgü oligonükleotid hibridizasyonla gcnotipleme metodu uygulandı. Kontrol grubuna kıyasla ÜK li hastalarda DRB1*1502 aleli ile pozitif (10/59 vs. 16/244, p=0.02, OR:2.9), DRB1*13 ile negatif (7/59 vs. 64/244, p=0.03, OR:0.38) ilişki olduğu gözlendi. Buna karşın Crohn hastalarında DRB1*08 sıklığı kontrole göre anlamlı bir artış gösterdi. Sonuçlar, ÜK ve CH nın genetik olarak farklı hastalıklar olduğu hipotezini desteklemektedir. Türkiye populasyonunda ÜK hastalığına yatkınlıkla direkt DRB1*1502 aleli veya bu aleli taşıyan haplotipin ilişkili olabileceği ileri sürülebilir.

Recently described distinct associations of HLA class II genes with ulcerative colitis and Crohn's disease suggest a genetic heterogeneity of disease susceptibility. In this study, HLA-DRB1 alleles were investigated in a population of UC (n=59) and CD (n=15) patients from Turkey compared to controls (n=244) with molecular genotyping by polymerase chain reaction and sequence specific oligonucleotide hybridization. We observed a positive association with the HLA-DRB1* 1502 allele (10/59 vs. 16/244, p=0.02, OR:2.9 ) and a negative association with the DRB1*13 allele (7/59 vs. 64/244, p=0.03, OR:0.38) in patients with UC, DRB1*08 allele increased significantly in patients with Crohn's disease compared to controls. These results support the hypothesis that UC and CD may be genetically distinct disorders. DRB1*1502 allele or haplotype bearing it, is associated with UC susceptibility in Turkish population.
The distribution of HLA DRB1alleles in inflammatory bowel disease patients in Turkey
Keywords: Genel ve Dahili Tıp